The Role of Digital Technology in Optimizing Marketing Strategies and Business Management in the Culinary Industry - Rizka Aisyah Nurjannah; Mena Sari; Julian Chandra; Jessica Asrina (Department of Business and Entrepreneurship, Faculty of Economics and Business, Universitas Negeri Makassar, 2024)
The rapid growth of the Indonesian food industry has been significantly driven by the strategic use of digital technology to optimize marketing and business management. This study examines the role of digital technology in enhancing these aspects within Yotta's culinary industry. Using a qualitative approach with a case study method, data was collected through in-depth interviews, observations, and document analysis. The findings reveal that digital technology plays a crucial role in improving operational efficiency, increasing brand awareness, and building stronger customer relationships, all of which contribute to increased sales and market reach. Additionally, the use of online platforms for food ordering, social media for marketing, and data analytics for decision-making has been effective in driving business growth. Digital tools have also improved inventory management, employee management, and financial control, leading to higher customer satisfaction and financial stability. The study concludes that optimal use of digital technology provides a significant competitive advantage in the food industry, with Yotta serving as a prime example of how digital innovation can enhance business performance.